2002
DOI: 10.1074/jbc.m111727200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Lymphotoxin-α but Not Tumor Necrosis Factor-α Reduces Atherosclerosis in Mice

Abstract: Inflammatory processes are involved with all phases of atherosclerotic lesion growth. Tumor necrosis factor-␣ (TNF␣) is an inflammatory cytokine that is thought to contribute to lesion development. Lymphotoxin-␣ (LT␣) is also a proinflammatory cytokine with homology to TNF␣. However, its presence or function in lesion development has not been investigated. To study the role of these molecules in atherosclerosis, the expression of these cytokines in atherosclerotic lesions was examined. The presence of both cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 55 publications
5
103
1
3
Order By: Relevance
“…Briefly, loss of the TNF gene did not alter atherosclerotic lesion development compared with wild-type mice, but LTA deficiency resulted in a 62% reduction in lesion size 29) ; however, genes up-regulated by LTA in the present study were almost identical to those induced by TNF 23) . These observations are possibly explained by the activation of TNFR and by TNF and LTA.…”
Section: Discussioncontrasting
confidence: 59%
“…Briefly, loss of the TNF gene did not alter atherosclerotic lesion development compared with wild-type mice, but LTA deficiency resulted in a 62% reduction in lesion size 29) ; however, genes up-regulated by LTA in the present study were almost identical to those induced by TNF 23) . These observations are possibly explained by the activation of TNFR and by TNF and LTA.…”
Section: Discussioncontrasting
confidence: 59%
“…Elevated serum levels of these cytokines are generally found in patients having a poor prognosis or more severe arterial lesions (55,56). Animal models designed to decipher the role of IL-6, TNF-a, and GM-CSF in atherosclerosis have not yet been fully conclusive because experimental settings (feeding diet, location of the lesions, and sex of the animals) largely determine the outcome of lesion evolution (57)(58)(59)(60)(61)(62)(63)(64). In this study we show that IL-6, TNF-a, and GM-CSF production is inconstant but characteristic of resident B cells, whereas the lack of expression of the other tested cytokines is a permanent feature.…”
Section: Discussionmentioning
confidence: 99%
“…This includes an important role of LT signaling in the acceptance of donor stem cells, controlling cuprizone-induced demyelination, the progression of experimental autoimmune encephalomyelitis and the control of lipid metabolism or liver regeneration Lo et al, 2007;Plant et al, 2007;Markey et al, 2009;Ruddell et al, 2009;Tumanov et al, 2009). Studies with different mouse models revealed a role of LTbR signaling in atherosclerosis development (Schreyer et al, 2002;Grabner et al, 2009) and an involvement of LTbR signaling was discovered in the pathogenesis of RA (Fava et al, 2003). Blocking LTbR signaling using a LTbR-Ig fusion protein could prevent the onset of collagen-induced arthritis or reduce its severity, depending on the time point of LTbR-Ig treatment (Fava et al, 2003).…”
Section: Depletion Of Lt Hi Expressing Cells and Curing Autoimmune DImentioning
confidence: 99%